Estimating the benthic efflux of dissolved iron on the Ross Sea continental shelf. Issue 21 (3rd November 2014) - Marsay, C. M.; Sedwick, P. N.; Dinniman, M. S.; Barrett, P. M.; Mack, S. L.; McGillicuddy, D. J.
Abstract Continental margin sediments provide a potentially large but poorly constrained source of dissolved iron (dFe) to the upper ocean. The Ross Sea continental shelf is one region where this benthic supply is thought to play a key role in regulating the magnitude of seasonal primary production. Here we present data collected during austral summer 2012 that reveal contrasting low surface (0.08 ± 0.07 nM) and elevated near‐seafloor (0.74 ± 0.47 nM) dFe concentrations. Combining these observations with results from a high‐resolution physical circulation model, we estimate dFe efflux of 5.8 × 107 mol yr−1 from the deeper portions (>400 m) of the Ross Sea continental shelf; more than sufficient to account for the inferred "winter reserve" dFe inventory at the onset of the growing season. In addition, elevated dFe concentrations observed over shallower bathymetry suggest that such features provide additional inputs of dFe to the euphotic zone throughout the year.